Persepsi Karyawan Laki-laki terhadap Pemimpin Perempuan: Apakah Pemimpin Perempuan Lebih Bersifat Asuh Daripada Pemimpin Laki-laki? - Djasmoredjo, Bene D.M. (Jurnal Widya Manajemen & Akuntansi, 2004)
The growing impact of working women has attracted researchers to conduct researches on the leadership style of women. Different leadership styles of men and women may affect employees' perception of their job. Male employees perceive that women tend lo use a transformational leadership style, especially on the idealized influence indication. This paper proves, that women have more nurture characteristic than men do. Woman, as a mother's figure, has shown the way she treats hq children When she becomes a leade4, this characteristic 'wttt stitl be with her in dealing with her employees. Stereotyped gender diferences do efist, eventhough some of their characteristics hne already changed.